Identification of variable lymphocyte receptors that can target therapeutics to pathologically exposed brain extracellular matrix - Umlauf, Benjamin J. (Sci Adv, 2019)
Diseases that lead to blood-brain barrier (BBB) disruption will pathologically expose normally inaccessible brain extracellular matrix (ECM) to circulating blood components. Therefore, we hypothesized that brain ECM-targeting moieties could specifically target the disrupted BBB and potentially deliver therapies. Variable lymphocyte receptors (VLRs) that preferentially associate with brain ECM were identified from an immune VLR library via yeast surface display biopanning coupled with a moderate throughput ECM screen. Brain ECM binding of VLR clones to murine and human brain tissue sections was confirmed. After systemic administration, P1C10, the lead brain ECM-targeting VLR candidate, specifically accumulated in brains with mannitol-disrupted BBB and at disrupted BBB regions in two different intracranial glioblastoma models. We also demonstrate P1C10’s ability to deliver doxorubicin-loaded liposomes, leading to significantly improved survival in glioblastoma-bearing mice. Thus, VLRs can be used to selectively target pathologically exposed brain ECM and deliver drug payloads.